2018
DOI: 10.1103/physrevd.98.124025
|View full text |Cite
|
Sign up to set email alerts
|

Strong cosmic censorship for the massless charged scalar field in the Reissner-Nordstrom–de Sitter spacetime

Abstract: It has recently been shown that the strong cosmic censorship conjecture can be violated by the massless neutral scalar field in the nearly extremal Reissner-Nordstrom-de Sitter black hole.However, the formation of such a black hole by gravitational collapse necessitates the presence of the charged sector on top of the Einstein-Maxwell system. Thus we numerically calculate the quasinormal modes for a massless charged scalar field in the Reissner-Nordstrom-de Sitter spacetime by generalizing the characteristic f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 26 publications
(34 reference statements)
7
62
0
Order By: Relevance
“…Recently, the validity of the Christodoulou version of SCC has been explored in asymptotically dS black holes by computing β for various perturbation fields [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In particular, a massless neutral scalar perturbation field in a Reissner-Nordstrom-de Sitter (RN-dS) black hole was considered in [30], and it was proven that SCC is violated in the near-extremal regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the validity of the Christodoulou version of SCC has been explored in asymptotically dS black holes by computing β for various perturbation fields [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In particular, a massless neutral scalar perturbation field in a Reissner-Nordstrom-de Sitter (RN-dS) black hole was considered in [30], and it was proven that SCC is violated in the near-extremal regime.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a massless neutral scalar perturbation field in a Reissner-Nordstrom-de Sitter (RN-dS) black hole was considered in [30], and it was proven that SCC is violated in the near-extremal regime. Since the charge matter is necessary for the formation of a charged black hole by gravitational collapse, the analysis was then extended to a charged scalar field in a RN-dS black hole [31][32][33], which showed that, in the highly extremal limit, there always exists a region in parameter space where SCC is violated. Although it was claimed in [34] that SCC would be saved for sufficiently large scalar field mass and charge, the existence of arbitrarily small oscillations of β around β = 1/2 was observed in a sufficiently near-extremal black hole [32].…”
Section: Introductionmentioning
confidence: 99%
“…To verify the reliability of the program, we calculated a series of lowest-lying QNMs in Table I. Comparing our results with that of RN-dS black holes [30,33], we find that they are consistent for large b (b = 10000).…”
Section: Numerical Resultsmentioning
confidence: 84%
“…Thus, in the presence of sufficiently charged particles, cosmic censorship can be saved (at least in anti-de Sitter spacetimes [26,27]). The situation in asymptotically de Sitter spacetimes remains unclear, as the presence of charged scalars and charged fermions do not seem to completely protect the cosmic censorship [28][29][30] -though it helps to some extent -despite some earlier evidences for such a claim [31,32]. The situation in the presence of a massless Dirac field were discussed in [33,34].…”
mentioning
confidence: 99%